A pilot survey of the current scope of the practice of South African physiotherapists in the intensive care units - H. van Aswegen; J. Patterson (AOSIS, 2005)
Objective: A pilot study was conducted to determine the current scope of practice of South African physiotherapists working in intensive care units in the government and the private sectors. These findings were compared to the findings from a European survey with regard to the role of the physiotherapist in European intensive care units. Methodology: Ninety questionnaires were distributed nationwide to secondary and tertiary government hospitals as well as to private practitioners involved in cardiopulmonary physiotherapy. The private practitioners included in this survey were listed in the Private Practitioners Association Official Members Directory. Junior and senior physiotherapists working in the intensive care units of their respective hospitals participated in completing the questionnaire. Comparisons between government and private sector data and between the South African survey and the European survey were carried out using the 2test for non-parametric data. A p-value of less than 0.05 was considered to be statistically significant. Results: Fifty-four questionnaires were analyzed and represented 60% of questionnaires sent out. Respondents to the South African survey reported 28% percent of all ICUs had between 9 - 12 beds; 83% physiotherapists indicated the availability of an on-call service during the night and 96% physiotherapists had a weekend physiotherapy service. Ninety-two percent of physiotherapists working in the government sector supervised students compared to 44% of physiotherapists in the private sector. Between 9% and 27% of physiotherapists in government and private hospitals actively participated in research in ICU. There were no statistically significant differences in the use of respiratory physiotherapy, mobilization and positioning between respondents to the European survey and those of the South African survey respectively. Conclusion: The response rate to this questionnaire was good. It was evident from this pilot survey that the scope of practice of physiotherapy in ICU didn't differ significantly between the government and private sector in South Africa. The role of the intensive care physiotherapist in South Africa was similar to that of the European physiotherapist  working in ICU.